Identification of mutations in the Wiskott-Aldrich syndrome gene and characterization of a polymorphic dinucleotide repeat at DXS6940, adjacent to the disease gene. - Kwan, S P (1995)
The Wiskott-Aldrich syndrome (WAS) is an X-chromosome-linked recessive disease characterized by eczema, thrombocytopenia, and immunodeficiency. The disease gene has been localized to the proximal short arm of the X chromosome and recently isolated through positional cloning. The function of the encoded protein remains undetermined. In this study we have characterized mutations in 12 unrelated patients to confirm the identity of the disease gene. We have also revised the coding sequence and genomic structure for the WAS gene. To analyze further the transmittance of the disease gene, we have characterized a polymorphic microsatellite at the DXS6940 locus within 30 kb of the gene and demonstrate the inheritance of the affected alleles in families with a history of WAS.